PENGENALAN PROSES DISTILASI MINYAK ATSIRI UNTUK MENDUKUNG PROGRAM DOUBLETRACK SMA BAHRUL MAGHFIROH, MALANG - Nirwana, Wa Ode Cakra; Sarosa, Aji Hendra; Nurhadianty, Vivi; Dewi, Luthfi Kurnia; Hapsari, Safrina; Bayu, Ardian Indra (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Bahrul Maghfiroh High School is located in Malang City. To manifest the school’s vision and mission, namely to produce graduates who are independent and have entrepreneurial skills, the school has a double-track program that aims to provide students with the skills to become entrepreneurs. Through this program, the school has succeeded in building business incubators, including the cultivation of mushrooms, quail, and fish, as well as coffee, chips, and yogurt processing. To support the double-track program, this community service activity aims to introduce the distillation process to students to produce essential oils, particularly citronella oil. This community service program was carried out in several stages, namely analyzing the school’s needs regarding the double-track program, providing training to students, evaluating participant satisfaction, and planning the sustainability of activities. Training activities include an explanation of the basic principles of distillation, a demonstration of distillation/refining to produce citronella oil on a laboratory scale, and a field trip to the mini plant of Institute Atsiri to learn the distillation process of essential oils on a pilot plant scale. The students and teachers were enthusiastic about participating in the entire series of events. Evaluation of student satisfaction shows that 36%, 48%, and 16% of students respectively, were very satisfied, satisfied, and neutral with this activity. Hopefully, this activity can become a business idea for schools and students. Abstrak SMA Bahrul Maghfiroh adalah SMA yang terletak di Kota Malang. Untuk mewujudkan visi misi sekolah yaitu mewujudkan lulusan yang mandiri dan terampil berwirausaha maka SMA ini memiliki program doubletrack yang bertujuan untuk membekali siswa dengan keahlian untuk berwirausaha. Melalui program ini, SMA Bahrul Maghfiroh berhasil membangun inkubator usaha diantaranya di bidang budidaya jamur, puyuh dan ikan serta pengolahan kopi, keripik dan yogurt. Untuk mendukung program doubletrack maka kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengenalkan proses distilasi/penyulingan kepada siswa untuk memproduksi minyak atsiri khususnya minyak sereh wangi. Program pengabdian kepada masyarakat ini dilaksanakan dengan beberapa tahapan yaitu menganalisis kebutuhan sekolah terkait program doubletrack, memberikan pelatihan kepada siswa, mengevaluasi kepuasan peserta, dan merencanakan keberlangsungan kegiatan. Pelatihan yang diberikan berupa penjelasan prinsip dasar distilasi, demo distilasi/penyulingan untuk menghasilkan minyak sereh wangi skala laboratorium dan kunjungan lapang ke mini plant Institut Atsiri untuk melihat proses penyulingan minyak atsiri skala pilot plant. Dalam kegiatan ini, siswa dan guru pendamping sangat antusias mengikuti seluruh rangkaian acara. Evaluasi tingkat kepuasan siswa dengan kegiatan ini menunujukkan bahwa 36% siswa merasa sangat puas, 48% merasa puas dan 16% netral. Diharapkan kegiatan ini dapat menjadi ide usaha bagi pihak sekolah maupun siswa.